Review of the Method of Valuation of the SDR. (Policy Papers; Policy Paper ;, 2015)
This paper provides the basis for the quinquennial review of the method of valuation of the Special Drawing Right (SDR). The review considers the composition, size, and weighting of the SDR currency basket and the financial instruments used to determine the SDR interest rate. The analysis in this paper is guided by the informal discussion of Executive Directors in July on initial considerations for the review. In light of Directors' preference, the two currency selection criteria for SDR inclusion are maintained. Since China continues to meet the export criterion, a key focus of this paper is on assessing whether the renminbi (RMB) could be determined to be a freely usable currency, which is the second criterion. The paper documents the rising international use and trading of the RMB since the 2010 SDR valuation review. A range of indicators suggests that use of the RMB in international transactions has risen substantially, albeit from a low base. The paper also finds that the RMB has become far more actively traded in foreign exchange markets, with sufficient depth to support operations of the size Fund members might undertake without an appreciable change in the exchange rate. Full Text also available in Chinese.